2014
DOI: 10.2147/oaap.s51741
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cold–dry (harmattan) season on colonic temperature and the development of pulmonary hypertension in broiler chickens, and the modulating effect of ascorbic acid

Abstract: The influence of cold-dry (harmattan) season on colonic temperature (CT) and the development of pulmonary hypertension (PH), as well as the effect of ascorbic acid (AA), were investigated in Anak male broilers during the harmattan season (November-January) of 2010-2013. A total of 150 broiler chickens per season served as subjects. At the age of 4 weeks, the broilers were randomly divided into two groups consisting of three replicates of 25 birds each: group I, the control, was not administered AA; group II wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…The lower mesor of RT recorded in sheep when the AT was 16 – 28°C during the harmattan season was in contrast to that recorded by Piccione et al [3], who found no effect of cold AT (9°C) or thermoneutral AT on mesor in sheep. The present result demonstrated the adverse effect of the harmattan season on the thermoregulation of sheep, and confirmed the earlier report that the harmattan season is the most thermally stressful of all the seasons prevailing in the Northern Guinea Savannah zone [57]. Although the AT (16 – 28.2°C) during the harmattan season was not as low as 9°C, its hypothermic effect on daily rhythmicity in RT of sheep was more severe than that recorded in Comisana sheep, exposed to cold AT of 9°C.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The lower mesor of RT recorded in sheep when the AT was 16 – 28°C during the harmattan season was in contrast to that recorded by Piccione et al [3], who found no effect of cold AT (9°C) or thermoneutral AT on mesor in sheep. The present result demonstrated the adverse effect of the harmattan season on the thermoregulation of sheep, and confirmed the earlier report that the harmattan season is the most thermally stressful of all the seasons prevailing in the Northern Guinea Savannah zone [57]. Although the AT (16 – 28.2°C) during the harmattan season was not as low as 9°C, its hypothermic effect on daily rhythmicity in RT of sheep was more severe than that recorded in Comisana sheep, exposed to cold AT of 9°C.…”
Section: Discussionsupporting
confidence: 92%
“…The harmattan season, characterized by cold-dry and dusty wind, blowing north-east and west off the Sahara desert into the Gulf of Guinea, has been shown to be the most thermally stressful season in the Northern Guinea Savannah zone [789]. …”
Section: Introductionmentioning
confidence: 99%
“…Yauri enjoys a Tropical Continental type of climate of which according to Köppen-Geiger climate classification is 'Aw' (Tropical Climate). This is largely controlled by two air masses, namely Tropical Maritime and Tropical Continental, blowing from the Atlantic and the Sahara Desert respectively (Minka and Ayo, 2013). Methodology Data for this study were collected from both primary and secondary sources.…”
Section: Land Degradation and Food Securitymentioning
confidence: 99%
“…During this process, the rubber sheets were hung on racks under shade. The experiments were conducted during the months of December and February (hamattan period in Nigeria), when the prevailing humidity is known to be lowest, within the range of 10% to 12% and wind velocity high [16]. In this condition, the samples were dried at ambient temperatures ranging from 27˚C -33˚C.…”
Section: Preparation Of Materialsmentioning
confidence: 99%